47-year-old female with an apical mass. Issue 11 (21st December 2016) - Andrews, Jack; Lang, Christopher CE; Dweck, Marc
Abstract : Clinical introduction: A 47-year-old female with no medical history presented with a sudden collapse. Physical examination, chest X-ray and high-sensitivity cardiac troponin I were normal, however ECG demonstrated anterior T-wave inversion. CT pulmonary angiography was performed which ruled out pulmonary embolism but revealed a non-calcified, homogenous mass at the left ventricular (LV) apex. It was not clear whether this mass was intramyocardial or pericardial. Transthoracic echocardiography confirmed the apical mass but was unable to establish its aetiology. Subsequent cardiac MR (CMR) demonstrated a highly vascular intramyocardial mass on perfusion imaging (Figure 1 A, online supplementary video A ), with striking, homogenous late gadolinium enhancement (Figure 1 B) consistent with a diagnosis of cardiac fibroma.1 The patient underwent successful surgical excision of the mass (see online supplementary image A ) and made a good symptomatic recovery, quickly mobilising around the ward. On examination, the patient was afebrile but had a blood pressure of 90/40 mm Hg and raised venous pressure. Postoperative imaging with echocardiography (see online supplementary video B ) and CMR (Figure 1 C, D and online supplementary video C ) revealed some unexpected findings. Study the provided images. Question: What is the next most appropriate management step? Antibiotic therapy for pericardial abscess Anticoagulation for LV thrombus Intravenous fluids with close clinical and imaging follow-up of the intramyocardial haemorrhage and pericardial haematoma Return to theatre for excision of residual tumour Urgent pericardiocentesis to drain pericardial collection